2017
DOI: 10.1111/ped.13258
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in use of contraindicated drugs with automated alerts in children

Abstract: Decreases in contraindicated drugs have accelerated after a regulatory action with automated alerts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The decrease in outpatient prescriptions suggests that the increase in the antibiotic rate can also be attributable to a shift in the drug utilization review policy in Korea that discourages prescriptions of many other drugs in pediatric patients. 17 In the present study, the usage of antibiotics fluctuated from year to year. The trend of antibiotic usage may have been affected by external factors.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The decrease in outpatient prescriptions suggests that the increase in the antibiotic rate can also be attributable to a shift in the drug utilization review policy in Korea that discourages prescriptions of many other drugs in pediatric patients. 17 In the present study, the usage of antibiotics fluctuated from year to year. The trend of antibiotic usage may have been affected by external factors.…”
Section: Discussionmentioning
confidence: 67%
“…Between 2010 and 2014, the number of antibiotic prescriptions increased while that of outpatient prescriptions decreased, contributing to the rise in the antibiotic rate. The decrease in outpatient prescriptions suggests that the increase in the antibiotic rate can also be attributable to a shift in the drug utilization review policy in Korea that discourages prescriptions of many other drugs in pediatric patients …”
Section: Discussionmentioning
confidence: 99%
“…The summary of characteristics of all the studies finally included was provided in Table 1. All included studies [18][19][20][21][22][23][24][25][26][27][28] evaluated the effects of the DUR system implemented in Korea, and the majority of study data used in these studies were Health Insurance Review and Assessment Service (HIRA) data. SO Kim et al 21) study analyzed National Health Insurance Service (NHIS) data to evaluate the DUR system, which were directly linked with HIRA data.…”
Section: Study Descriptionmentioning
confidence: 99%
“…These three studies showed the effects of implementing DUR system on the trend of pharmaceutical expenditures without indicating specific types of medications they analyzed. Two studies 19,22) found contraindicated use trends for drug-drug interactions after implementation of DUR system, and six studies 19,[23][24][25]27,28) described outcomes related to age-contraindicated drug uses. SO Lee et al, 19) JH Yang et al, 25) JH Heo et al 18) studies provided the outcomes after the DUR system implemented.…”
Section: Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation